2007
DOI: 10.1007/s10397-007-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic excision of a large ovarian cyst

Abstract: Keywords Large ovarian cyst . Laparoscopic management and ovarian cyst Case reportWe present a case of laparoscopic drainage and excision of a large ovarian cyst. A 22-year-old, nulliparous woman presented to a general practitioner with occasional rightsided upper abdominal pain. An abdominal ultrasound was arranged to assess the biliary system. However, the scan identified a huge ovarian cyst filling the entire abdominal cavity from the epigastrium to the pouch of Douglas. An urgent review was arranged at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…On nal pathological reports, two cysts were mucinous cystadenomas and four were serous cystadenomas [8]. Rabbani et al reported in a case report of a huge ovarian cyst the use of a Veres needle to aspirate and drain the contents of the cyst and perform a cystectomy [9]. A. Alobaid et al described a case series of 5 patients with huge ovarian cysts successfully managed by laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…On nal pathological reports, two cysts were mucinous cystadenomas and four were serous cystadenomas [8]. Rabbani et al reported in a case report of a huge ovarian cyst the use of a Veres needle to aspirate and drain the contents of the cyst and perform a cystectomy [9]. A. Alobaid et al described a case series of 5 patients with huge ovarian cysts successfully managed by laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Leakage of the cyst contents may result in chemical peritonitis or dissemination of cells in the case of malignant tumour [1, 3]. Although the significance of this leakage is controversial, we suggest avoiding it whenever possible [3, 5, 7]. This can be achieved in our opinion by percutaneous drainage of the cyst and insertion of the first trocar according to the Hasson technique [8].…”
Section: Discussionmentioning
confidence: 99%